The butterfly Danaus chrysippus (Lepidoptera: Nymphalidae) in Kenya is variably infected with respect to genotype and body size by a maternally transmitted male-killing endosymbiont (Spiroplasma) - Herren, J; Gordon, I; Holland, P; Smith, D (2007)
Female-biased sex ratios in Danaus chrysippus (Linnaeus) (family Nymphalidae, subfamily Danainae, tribe Danaini) populations are attributed to the action of an endosymbiotic 'male-killer' bacterium of the genus Spiroplasma. In stark contrast to the extensive geographic range of their host, the Spiroplasma appears to be restricted to East Africa, where four African D. chrysippus subspecies exist sympatrically and form a hybrid zone. In this study, specimens collected at three sample sites within the hybrid zone were screened for Spiroplasma infection. The findings demonstrate that, within the hybrid zone, the frequency of Spiroplasma infection varies both spatially and temporally. Host genotype at three biallelic wing pattern loci, representative of subspecific genetic divergence, is correlated to Spiroplasma infection. Linkage between the frequency of the recessive a allele and Spiroplasma is established, suggesting the presence of a linked allele controlling infection susceptibility. In addition, a negative correlation between D. chrysippus forewing length and Spiroplasma infection is identified, suggesting that infection has a deleterious effect on body size. © 2007 ICIPE.